(untitled) (Journal of Current and Advance Medical Research, 2014)
Background: Treatment of comminuted intra-articular fractures of distal radius by external fixator is an important. Objective: The aim of study was to investigate the usefulness of external fixator as a treatment option for displaced comminuted intra-articular fractures of distal radius. Methodology: This case series was conducted in the Department of orthopaedic Surgery at Shaheed Suhrawardy Medical College& Hospital, Dhaka during the period of November 2011 to July 2013. All the patients having comminuted intra-articular distal radial fractures were being treated with mini uniaxial external fixator under brachial plexus block. The average follow up was performed in about 6 month. Result: A total number of fifteen patients were enrolled for this study. The mean age with SD was 50.21±9.473. Patient outcomes were measured by modified Knirk and Jupiter score and were categorized as satisfactory and unsatisfactory groups. In this study satisfactory outcome was found in 86.0%. All fractures (100.0%) were united nicely. Few complications were encountered. Postoperative osteoarthritis was not found during follow up. Conclusion: The use of external fixator for treating the comminuted intra-articular distal radial fractures produces satisfactory result. DOI: http://dx.doi.org/10.3329/jcamr.v1i2.20516 Journal of Current and Advance Medical Research Vol.1(2) 2014: 30-34